DIGITAL MARKETING: ENGAGING CONSUMERS WITH SMART DIGITAL MARKETING CONTENT - Zakiya Umami; Gede Sri Darma (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2021)
The accelerated development of digital technology is currently affected by several factors such as the use of internet technology, the development of smartphones, the emergence of various social media, the development of e-commerce and the large number of people who actively use the internet. This study aimed to find a suitable marketing strategy for promoting food products by observing the development of digital marketing, especially today’s social media marketing. Bali was well known as one of the destinations visited by local and International tourists. One restaurant located in Kuta called Maisyaroh, in spite of the advancement of digital technology, had not optimized the use of the technology well. Whereas, it actually could affect the competitive advantages. In addition, a qualitative descriptive approach was used in this research, while the data collection techniques were carried out through observation, in-depth interviews by using Zoom Meeting and documentation. The results stated that promotion using Instagram (IG) endorsement and paid promote could increase brand awareness and buying interest.